Blackouts eaudiobook A novel. - Torres, Justin (Macmillan Audio, 2023)
Winner of the National Book Award for Fiction A Best Book of the Year: The Washington Post , Time , BookPage A Must-Read: The New York Times , Time, Los Angeles Times , Chicago Tribune , The Guardian , Boston Herald , Literary Hub , The Rumpus , The Bay Area Reporter , Datebook , Electric Literature , The Stacks , Them , Publishers Weekly "Sweeping, ingenious . . . A kiss to build a dream on." —Maureen Corrigan, NPR's Fresh Air From the bestselling author of We the Animals , Blackouts mines lost histories—personal and collective. Out in the desert in a place called the Palace, a young man tends to a dying soul, someone he once knew briefly, but who has haunted the edges of his life. Juan Gay—playful raconteur, child lost and found and lost, guardian of the institutionalized—has a project to pass along to this new narrator. It is inspired by a true artifact of a book, Sex Variants: A Study in Homosexual Patterns , which contains stories collected in the early twentieth century from queer subjects by a queer researcher, Jan Gay, whose groundbreaking work was then co-opted by a committee, her name buried. As Juan waits for his end, he and the narrator trade stories—moments of joy and oblivion—and resurrect lost loves, lives, mothers, fathers, minor heroes. The past is with us, beside us, ahead of us; what are we to create from its gaps and erasures? Inspired by Kiss of the Spider Woman , Pedro Páramo , Voodoo Macbeth , the book at its own center and the woman who created it, oral histories, and many more texts, images, and influences, Justin Torres's Blackouts is a work of fiction that sees through the inventions of history and narrative. An extraordinary work of creative imagination, it insists that we look long and steady at the world we have inherited and the world we have made—a world full of ghostly shadows and flashing moments of truth. A Macmillan Audio production from Farrar, Straus and Giroux.